2020
DOI: 10.1186/s12935-020-01483-6
|View full text |Cite
|
Sign up to set email alerts
|

MiR-145-5p suppresses the proliferation, migration and invasion of gastric cancer epithelial cells via the ANGPT2/NOD_LIKE_RECEPTOR axis

Abstract: Objective: This study aimed to investigate the relationship among miR-145-5p, ANGPT2 and the NOD_LIKE_RECEP-TOR pathway, thereby revealing the molecular mechanism of these three factors underlying the proliferation, migration and invasion of gastric cancer (GC) epithelial cells. Methods: qRT-PCR was carried out to detect the expression of miR-145-5p and ANGPT2 mRNA. Western blot was performed to test the protein levels of ANGPT2 as well as NOD1, NOD2 and NF-κB in the NOD_LIKE_RECEPTOR pathway. The targeting re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…In assessing tumor repression mechanism, the present study hypothesized a regulation of PCa biological activities via corresponding genes’ modulation. Previous investigations have outlined genes such as MYO6 [ 31 ], ANGPT2 [K. 32 ], and TGF-β1 [Y. 33 ] as the ultimate target of miR-145.…”
Section: Discussionmentioning
confidence: 99%
“…In assessing tumor repression mechanism, the present study hypothesized a regulation of PCa biological activities via corresponding genes’ modulation. Previous investigations have outlined genes such as MYO6 [ 31 ], ANGPT2 [K. 32 ], and TGF-β1 [Y. 33 ] as the ultimate target of miR-145.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in addition to RP11-354B3.1, we found that miR-145-5p and one of its’ target genes MAPK4 were listed in the top candidates ( Figure 5A ). Combined with the above GSEA analysis results, we chose miR-145-5p and MAPK4 for further validation because several studies had revealed the tumor suppressive function of miR-145-5p in GC cells ( Li et al, 2020 ; Zhou et al, 2020 ). More importantly, MAPK4 is key regulator in the JNK and ERK signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Many researches had revealed that miR-145-5p exerted an inhibitory impact on a series of tumor growth. 26–28 Zhou et al marked that miR-145-5p repressed cell invasion, migration, and proliferation of gastric cancer cells through targeting ANGPT2 and modulating the NOD_LIKE_RECEPTOR pathway. 26 Moreover, circRNA circ_0058063 sponged miR-145-5p to elevate CDK6 expression, thereby accelerating cell migration and growth in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 26–28 Zhou et al marked that miR-145-5p repressed cell invasion, migration, and proliferation of gastric cancer cells through targeting ANGPT2 and modulating the NOD_LIKE_RECEPTOR pathway. 26 Moreover, circRNA circ_0058063 sponged miR-145-5p to elevate CDK6 expression, thereby accelerating cell migration and growth in bladder cancer. 27 Furthermore, miR-145-5p played a suppressive effect on hepatocellular cancer growth.…”
Section: Discussionmentioning
confidence: 99%